Application of the Modified Page-Hinkley Test to Diagnose Current Sensor Faults in Induction Motor Drives - Tran, Cuong Dinh; Kuchar, Martin; Nguyen, Phuong Duy (Engineering, Technology & Applied Science Research, 2026)
This paper investigates improving reliability in Induction Motor (IM) drives using the Field-Oriented Control (FOC) technique by developing a Modified Page–Hinkley Test (MPHT) for real-time detection of Current Sensor Faults (CSFs). The proposed method monitors the absolute residual between the measured stator current and the corresponding estimated obtained value from a Luenberger Observer (LO). The modified test is implemented in a stepwise manner to ensure high sensitivity to faults and robustness against measurement noise. Upon fault detection, the observer seamlessly reconstructs the faulty current signal to maintain stable closed-loop operation without re-tuning the controller. Simulation studies performed in MATLAB/Simulink under various types of soft (drift, scale, offset, precision degradation), and hard (constant value, constant with noise) faults confirm fast fault detection, accurate fault isolation, and stable system performance. The results show that the proposed method provides a practical and efficient solution for IM drive systems under dynamic operating conditions.